COMPARATIVE STATISTICAL APPROACH FOR THE ASSESSMENT OF POLLUTION OF HEAVY METALS IN RAWAL LAKE WATER AND MAIN STREAMS ENTERING RAWAL LAKE (Biological Sciences - PJSIR, 2003)
This study was conducted to assess the distribution of heavy metals (Cr, Co, Cd, Zn, Ni, Cu, Mn and K) in water and liquid waste samples at different stations of Rawal Lake and main streams entering Rawal Lake (Pakistan). The samples were analyzed by flame atomic absorption spectrophotometer. The results were discussed in view of quality standards set by Environmental Protection Agency. At most sites of Rawal Lake, concentration of Ni was relatively high and exceeded the permitted levels. Statistical methods of relevance to the trace metal data have been applied such as standard deviation, average concentration and correlation coefficients for investigating the distribution pattern of metals in water and liquid waste system.